Vaginal mucus impedance as an aid for prediction of optimum time for breeding during estrus in cows - SHARMA, PRASHANT; TIWARl, R P; SINGH, MOHAN; SAHU, S K; YADAV, S K (The Indian Journal of Animal Reproduction, 2023)
Experiment using inravaginal probe with impedance meter was conducted to observe the pattern of vaginal mucus impedance (VMI) during estrus. Fertility rates in cows inseminated with different hours during estrus were analysed to correlate the VMI dring insemination with fertility. VMI during estrus was measured 6 hourly for 24 hrs in experimental cows (n=l0) with external signs of estrus. During estrus itself there was variation in VMI in different hours. The VMI at 0, 6, 12, 18 and 24 hrs after onset of estrus were 41.2±0.76, 38.5±1.38, 33.7±0.83, 42.25±0.85 and 50.3±0.58 ohms respectively. The lowest VMI was recorded 12 hrs after onset of estrus VMI was significantly lowered from O hrs to 6 hrs (P < 0.05) and to 12 hrs (P < 0.01) while it was significantly increased from O hr to 24 hrs after onset of estrus. Chi-square analysis of results shows significant association (P < 0.01) between VMI and non-return rates in animals (n = 56) inseminated during estrus with low impedance value (25-34 ohms). There was also the significant association (P < 0.05) between VMI and pregnancy rates as detected on day 60 after insemination by rectal palpation.